Pengembangan Modul Tematik Praksis Sastra Anak pada Pembelajaran Drama Berbasis Karakter Nasionalisme di SD - Sendi Fauzi Giwangsa; Dwi Heryanto; Tatat Hartati; Effy Mulyasari; Rina Heryani; Evi Rahmawati; Faisal Sadam Muron; Mubarok Somantri (Elementary Teacher Education Program, Majalengka University, 2023)
This research aims to reconstruct and integrate character values with literary appreciation through developing modules on drama learning due to students' lack of interest in learning and emphasis on learning success seen from high grades or learning outcomes, thus eliminating the essence of education to instill character values. The method used in this research is a qualitative research method with a development model designed by Richey and Klein, namely Design and Development (D&D) which refers to the PPE model. The data collection technique uses a validation sheet given to experts once, involving 7 learning experts and material experts as participants. Analyzed descriptively so that improvements are made to obtain the final design. With the validation results, the overall score from the experts was 94% in the